Associations among Different Internet Access Time, Gender and Cyberbullying Behaviors in Taiwan’s Adolescents - Chao, Cheng-Min; Yu, Tai-Kuei (Frontiers in Psychology, 2017)
With the increasing convenience of social networking sites and their interconnectedness with human interaction, verbal and image bullying have turned digital, making cyberbullying a new form of bullying attracting the attention of researchers, social workers, and schools. This study focuses on the status quo of attitude toward cyberbullying and cyberbullying behaviour, explores associations of attitude toward behavior on cyberbullying behaviour in gender and different internet access times. In a cross-sectional survey, adolescents were surveyed through self-report questionnaires, 13,864 respondents were received among 150 high schools in Taiwan. Statistical analyses were performed using structural equation modeling (SEM). The study revealed that attitude toward cyberbullying has a direct effect on cyberbullying behaviour; among the greatest direct impact were when students use the Internet during the time frame 10:00-14:00. Parents and schoolteachers pay special attention to students using the Internet during this time frame 10:00-14:00 and give guidance, express care, and help those being bullied to communicate and use the Internet in a correct manner. Among genders, male student attitude towards behaviour has a greater effect than those of female students. Both male and female students know what cyberbullying is and have witnessed, heard of, or personally encountered cyberbullying behaviour. We recommend students talk to parents or teachers or other people who care to reduce the negative effects of cyberbullying. We hopeful that the conceptualization model presented in this study serves as an activator for researches on attitude toward cyberbullying and cyberbullying behaviour, and serves a guide and a call to attract more researches in this area.